Implementation Of E-SCM Efforts To Improve Distribution Management Efficiency - Diatri Arditia Arini; Nurul Rahmadani; Suparmadi Suparmadi (Pusat Teknologi Informasi dan Pangkalan Data IAIN Syekh Nurjati Cirebon, 2025)
This research focuses on the design and implementation of an Electronic Supply Chain Management (E-SCM) system to enhance efficiency and responsiveness in distribution and inventory management within the agricultural sector. The study addresses recurring challenges in supply chain operations, including inefficiencies in inventory tracking, lack of coordination and transparency between suppliers and customers, and difficulty in forecasting demand due to fluctuating market conditions, seasonal cycles, and environmental factors. These challenges often result in stock imbalances, delayed deliveries, increased operational costs, and diminished customer satisfaction. The proposed solution is a web-based platform integrating administrators, suppliers, and customers into a single digital ecosystem. It allows users to place orders, monitor real-time stock availability, and generate dynamic reports, thereby improving coordination, transparency, and decision-making across the supply chain. Adopting a qualitative methodology, data were collected through direct observation, structured interviews, document analysis, and a literature review. The system was developed using PHP for server-side programming, MySQL for database management, and Visual Studio Code as the primary development environment. System validation through black-box testing confirmed that all functional and usability requirements were met. The implementation results demonstrate that the E-SCM system improves distribution management efficiency by approximately 35%, reduces manual inventory errors by over 40%, and significantly enhances responsiveness to demand fluctuations. Additionally, it strengthens engagement between suppliers and customers by enabling transparent communication and immediate access to accurate data. The findings indicate that E-SCM adoption can serve as a strategic enabler for small and medium-sized enterprises (SMEs) to optimize supply chain performance, reduce logistical inefficiencies, and achieve sustainable growth in a competitive digital economy